Larvicidal Activity of Bay Leaf (Syzygium polyanthum) Ethanolic Extract in Addition of PEG Diluent on Aedes aegypti Larvae : Aktivitas Larvasida Ekstrak Ethanol Daun Salam (Syzygium polyanthum) Dengan Penambahan Pengencer PEG Terhadap Larva Nyamuk Aedes aegypti - Dewi, Listiana Masyita; Salsabila, Tasya Viona; Bestari, Rochmadina Suci; Wahyuni, Sri (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Dengue Fever (DF) is a viral infection disease transmitted by Aedes aegypti. It is one of Indonesian endemic diseases that reported to occur throughout the year. To break the transmission chain of DF, the use of larvicides is preferred, especially using natural ingredients, such as bay leaves (Syzygium polyanthum). Polyethylene glycol (PEG) as a dispersant may prevent the clumping of material test so that it can be distributed evenly in water which is the medium of growth for larvae. Objectives: To determine the effectiveness of ethanolic extract of bay leaves (EEBL) in addition of PEG diluent on the mortality of Aedes aegypti larvae. Material and Method: Bay leaves as the main material were extracted using 96% of ethanol, and were applied in two variation concentration, 0.75% and 1%, while the diluent added was PEG. The samples used in this study were Aedes aegypti larvae at stages III-IV, with a total of 25 individuals for each treatment group. Evaluation was performed every 6 hours, for 24 hours, then the results were recorded and analyzed using the Kruskall Wallis test and the Mann Whitney test. Result: In both of variation concentration used, at 24 hours of observation it was obtained the mortality of Aedes aegypti larvae was 100%. The p-value obtained for the Kruskall Wallis test was <0.05. From Mann Whitney test, when each of treatment group was compared to the positive control, abateÂ®, the p-value obtained is >0.05, while when they were compared to the negative control, PEG, the p-value obtained is <0.05. Conclusion: 96% ethanolic extract of bay leaves in addition of PEG diluent is effective as Aedes aegypti larvicides. It is also known that EEBL at concentration of 0.75% and 1% in addition of PEG are as effective as abateÂ® as Aedes aegypti larvicides.